Cortical Surface Parcellation Based on Graph Representation of Short Fiber Bundle Connections - Silva, Felipe; Guevara, Miguel; Poupon, Cyril; Mangin, Jean-Francois; Hernandez, Cecilia; Guevara, Pamela (Proceedings (International Symposium on Biomedical Imaging), 2019)
We propose a new automatic algorithm for the tractography-based parcellation of the cortical surface. The method is based on segmented bundles of the superficial white matter (SWM), calculated for each subject, using a multi-subject SWM bundle atlas. The scheme uses a fast intersection algorithm to define cortical regions connected by each bundle and then it defines a graph representation to model the overlapping of the regions to derive the final parcellation. The algorithm was tested on one subject, and resulting parameters were applied to other 4 subjects. Results show a good correspondence between subjects.